Burden of invasive group B Streptococcus disease and early neurological sequelae in South African infants. - Ziyaad Dangor (PLoS ONE, 2015)
Group B Streptococcus (GBS) is a leading cause of neonatal sepsis and meningitis. We aimed to evaluate the burden of invasive early-onset (0-6 days of life, EOD) and late-onset (7-89 days, LOD) GBS disease and subsequent neurological sequelae in infants from a setting with a high prevalence (29.5%) of HIV among pregnant women.A case-control study was undertaken at three secondary-tertiary care public hospitals in Johannesburg. Invasive cases in infants <3 months age were identified by surveillance of laboratories from November 2012 to February 2014. Neurodevelopmental screening was done in surviving cases and controls at 3 and 6 months of age.We identified 122 cases of invasive GBS disease over a 12 month period. Although the incidence (per 1,000 live births) of EOD was similar between HIV-exposed and HIV-unexposed infants (1.13 vs. 1.46; p = 0.487), there was a 4.67-fold (95%CI: 2.24-9.74) greater risk for LOD in HIV-exposed infants (2.27 vs. 0.49; p<0.001). Overall, serotypes Ia, Ib and III constituted 75.8% and 92.5% of EOD and LOD, respectively. Risk factors for EOD included offensive draining liquor (adjusted Odds Ratio: 27.37; 95%CI: 1.94-386.50) and maternal GBS bacteriuria (aOR: 8.41; 95%CI: 1.44-49.15), which was also a risk-factor for LOD (aOR: 3.49; 95%CI: 1.17-10.40). The overall case fatality rate among cases was 18.0%. The adjusted odds for neurological sequelae at 6 months age was 13.18-fold (95%CI: 1.44-120.95) greater in cases (13.2%) than controls (0.4%).The high burden of invasive GBS disease in South Africa, which is also associated with high case fatality rates and significant neurological sequelae among survivors, is partly due to the heightened risk for LOD in infants born to HIV-infected women. An effective trivalent GBS conjugate vaccine targeted at pregnant women could prevent invasive GBS disease in this setting.